The Microstructure and Thermal Conductivity of Pressureless Infiltrated SiCp/Al Composites Containing Electroless Nickel Platings - Aihua Zou; Xianliang Zhou; Xiaozhen Hua; Duosheng Li; Kaiyang Wu (Advances in Materials Science and Engineering)
A nickel (Ni) coating was deposited on the surface of silicon carbide particles (SiCp) through electroless plating and we characterized the morphology and phase structure of the coating and the pressureless infiltrated SiCp/Al composites. The effect of Ni coatings on the thermal conductivity of the composites was examined and analyzed with three-dimensional video microscope, scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction microscope (XRD), and finite-element. The results show that a continuous and uniform coating with a certain thickness (around 3.5 μm) can be formed on the surface of SiCp. With the addition of the Ni layer, there are some intermetallics Ni3Al but no interfacial carbide Al4C3, which improves the wettability and the thermal conductivity of the composites. The experiments and simulations both show that Ni coatings do not substantially decrease the overall thermal conductivity of the composite, although the thermal conductivity of Ni itself is lower than Al and SiC by a factor of 1.